A Minimal Load‐and‐Lock RuII Luminescent DNA Probe. Issue 38 (11th August 2021) - Newton, Matthew D.; Fairbanks, Simon D.; Thomas, Jim A.; Rueda, David S.
Abstract: Threading intercalators bind DNA with high affinities. Here, we describe single‐molecule studies on a cell‐permeant luminescent dinuclear ruthenium(II) complex that has been previously shown to thread only into short, unstable duplex structures. Using optical tweezers and confocal microscopy, we show that this complex threads and locks into force‐extended duplex DNA in a two‐step mechanism. Detailed kinetic studies reveal that an individual stereoisomer of the complex exhibits the highest binding affinity reported for such a mono‐intercalator. This stereoisomer better preserves the biophysical properties of DNA than the widely used SYTOX Orange. Interestingly, threading into torsionally constrained DNA decreases dramatically, but is rescued on negatively supercoiled DNA. Given the "light‐switch" properties of this complex on binding DNA, it can be readily used as a long‐lived luminescent label for duplex or negatively supercoiled DNA through a unique "load‐and‐lock" protocol. Abstract : Using single‐molecule optical tweezers and confocal microscopy we perform kinetic analysis of a novel dinuclear ruthenium(II) DNA imaging probe. Reversable binding is observed on relaxed DNA, however on stretching DNA, threading can occur, resulting in high affinity stable binding. Threading is highly stereoisomer specific and dependent on DNA supercoiling state. This DNA probe has exciting potential for DNA structure specific imaging.